2020
DOI: 10.5650/jos.ess20030
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Acylglutamic Acid-Alkylamine Complexes in Aqueous Media

Abstract: IntroductionGemini surfactant is a dimer of monomeric surfactants linked by a space unit, being composed of two hydrophilic headgroups and two hydrophobic chains in a molecule 1, 2 . Gemini surfactants have been attracted as a new type of surfactants because of their excellent micellization efficiency at low concentrations and good solubility in water 1, 2 . Thus, gemini surfactants are generally categorized into an eco-friendly surfactant. However, their synthesis and purification processes are usually compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…N -Dodecanoylglutamic acid (C12Glu) was synthesized according to the procedure described in our previous papers. , C12Glu was neutralized using NaOH at a fixed mole ratio, C12Glu:NaOH = 1:2, to yield C12Glu-2Na. C16OH and NaCl were purchased from FUJIFILM Wako Pure Chemical Corporation and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…N -Dodecanoylglutamic acid (C12Glu) was synthesized according to the procedure described in our previous papers. , C12Glu was neutralized using NaOH at a fixed mole ratio, C12Glu:NaOH = 1:2, to yield C12Glu-2Na. C16OH and NaCl were purchased from FUJIFILM Wako Pure Chemical Corporation and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…For amino acid-based surfactant aqueous solutions, as literatures reported (Faustino et al, 2011;Ghosh & Ray, 2014;Lu et al, 2015;Sakai et al, 2012Sakai et al, , 2016Vu et al, 2020;Yoshikawa et al, 2020), another approach to building viscosity without polymer additives is by formulating them under appropriate pH conditions, in which the low pH is favorable for the formation of longer-range structures including wormlike micelles. Therefore, the effect of pH on steady-shear viscosity at varying shear rate was investigated in 10 wt% SLSar/ water/5 wt% C12P and 15 wt% SLSar/water systems.…”
Section: Effect Of Phmentioning
confidence: 99%
“…triethyleneglycol alkyl ether (Shrestha et al, 2008;Shrestha et al, 2009aShrestha et al, , 2009b, alkanolamide, and monoglycerides. More recently, Sakai et al reported a novel way to acquire highly viscoelastic micellar solutions by a series of pseudogemini amino acid-based surfactants, which fabricated from nonsurface-active compounds, such as alkylamine, dodecyldimethylamine, and dodecylmethylamine, upon acidÀalkali reaction with acylglutamic acid (Sakai et al, 2012(Sakai et al, , 2016Yoshikawa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%